Disaster, Involution, and Dependency: a Socio-Economic Analysis of the 1861 Flood in the Residency of Bagelen - Diki Kristiyadi; Rhoma Dwi Aria Yuliantri (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This study investigates the catastrophic flood disaster that struck the Residency of Bagelen in February 1861, conceptualizing it not merely as a natural phenomenon but as a consequence of inherent structural socio-economic vulnerabilities under colonialism. By applying Clifford Geertz’s theoretical framework of Agricultural Involution and Raúl Prebisch’s Dependency theory, this research aims to thoroughly analyze the multidimensional impacts of the tragedy. The methodology used is historical analytical, drawing upon primary sources such as the Koloniaal Verslag (Colonial Report) and colonial newspapers, alongside secondary sources like academic journals. The findings indicate that Bagelen sustained the most severe losses compared to other residencies. These losses stemmed from agricultural intensification during the Cultuurstelsel (Cultivation System), which fostered agricultural involution, thereby creating a precarious socio-economic system highly susceptible to external shocks, such as a disaster. Ironically, the Colonial Government's response with involving massive financial allocations and spatial restructuring functioned primarily as a strategy of exploitation. This measure, rather than building local self-sufficiency, reproduced and reinforced the existing system of economic dependency. The remarkable social resilience demonstrated by local communities in their self-recovery, a characteristic of societies affected by agricultural involution, was ultimately exploited by the colonial power to ensure continued exploitation and the flow of profits, thereby maintaining Bagelen in colonial dependency. This confirms that the scale of destruction and the impact of the 1861 disaster were the result of a systemic failure of the colonial socio-economic order.